Application of lactic acid bacteria to improve the food safety of sago starch - Tryanisa Ridla Amalia; Titi Candra Sunarti; Anja Meryandini (Menara Perkebunan, 2024)
Sago starch production in local industries is still carried out traditionally and uses poor-quality water. This production causes sago starch to be fermented spontaneously, resulting in sour sago and possibly contamination by pathogenic bacteria. Lactic acid bacteria (LAB) can produce lactic acid and are suitable for use as a starter. Adding LAB as a starter in sago starch fermentation is expected to reduce the number of pathogenic bacterial growths, thereby increasing food safety in sago starch. This research aimed to obtain LAB and evaluate their use in sago starch fermentation to improve food safety. LAB selection was conducted by testing the LAB tolerance ability to low pH and the adaptability of the LAB growth in sago starch. This study was carried out using and without a LAB liquid starter. The water source during the fermentation originated from drinking water and the sago starch industrial factory. The fermentation was carried out for ten days at room temperature with an observation every two days. The results showed that fermented sago starch using drinking water did not harbor E. coli, Salmonella, or Shigella bacterial contamination. In contrast, sago starch fermented using water from the factory harbored these bacterial contaminations. Adding LAB IL1 isolate as a starter in fermentation showed the ability to reduce the number of pathogenic bacteria in sago starch.